PRINCIPALS’ FORMATIVE ASSESSMENT STRATEGIES AND CURRICULUM IMPLEMENTATION IN PUBLIC JUNIOR SCHOOLS IN SOTIK SUB-COUNTY, KENYA - Betty Jepkeitany Kapkiai; Dr. Joshua Manduku; Dr. Dorothy Soi (EPRA International Journal of Environmental Economics Commerce and Educational Management, 2026)
Effective curriculum implementation requires instructional practices that enable teachers to respond to learner needs and align teaching with curriculum expectations. Formative assessment provides a mechanism through which evidence of learner progress can inform feedback and instructional adjustment; however, evidence on its contribution to curriculum implementation in Kenya's junior secondary schools remains limited. This study examined the relationship between formative assessment and curriculum implementation in public junior secondary schools in Sotik Sub-County, Kenya. Guided by the Psychological Theory of Supervision, the study adopted a convergent mixed-methods design. Data were collected from teachers using questionnaires and from principals through interviews. Quantitative data were analysed using descriptive statistics, Pearson correlation, and simple linear regression, while qualitative data were analysed thematically. The findings revealed a strong, positive, and statistically significant relationship between formative assessment and curriculum implementation (r = 0.661, p < 0.001). Formative assessment significantly predicted curriculum implementation, accounting for 43.7% of its variance (R² = 0.437). Qualitative findings corroborated the quantitative results, showing that the use of learner performance data, feedback, and instructional adjustment supported responsive curriculum delivery. However, self-assessment and reflective practices were less consistently implemented, indicating that participatory dimensions of formative assessment remain underdeveloped. The study concludes that formative assessment contributes to curriculum implementation when assessment evidence is systematically translated into feedback and instructional action. The findings highlight the need for stronger professional and institutional support for assessment-informed instruction and reflective practice in junior secondary schools.